1995
DOI: 10.1111/j.1553-2712.1995.tb03220.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Drug Therapy with Survival in Cardiac Arrest: Limited Role of Advanced Cardiac Life Support Drugs

Abstract: Initiating cause of arrest, time to ACLS, and duration of ACLS were important correlates of survival. Other than procainaimide, standard ACLS drugs had relatively little association with survival, but timing of administration may be an important factor. Further research using definitive large randomized controlled trials is warranted to assess the role of drug therapy in improving cardiac arrest survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 42 publications
2
51
0
3
Order By: Relevance
“…209 One study documented improvement in ROSC (14% versus 0%) when atropine was given to adults in asystolic out-of-hospital cardiac arrest in combination with epinephrine and sodium bicarbonate, but none survived to discharge (LOE 3). 211 Three studies suggested that the use of atropine for treatment of cardiac arrest was not associated with any change in survival (LOE 2 212 ; LOE 5 213,214 ). Four human studies suggested that the use of atropine was associated with poor survival (LOE 4).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…209 One study documented improvement in ROSC (14% versus 0%) when atropine was given to adults in asystolic out-of-hospital cardiac arrest in combination with epinephrine and sodium bicarbonate, but none survived to discharge (LOE 3). 211 Three studies suggested that the use of atropine for treatment of cardiac arrest was not associated with any change in survival (LOE 2 212 ; LOE 5 213,214 ). Four human studies suggested that the use of atropine was associated with poor survival (LOE 4).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…In urgent situations, up to 50 mg/min may be administered to a total dose of 17 mg/kg. Use of procainamide in pulseless VT/VF is supported by a retrospective comparison study involving only 20 patients 120 and is limited by the need to infuse the agent relatively slowly. The potential hazard of more rapid (bolus) administration during overt cardiac arrest must be balanced against the attendant risks and requires further study.…”
Section: Procainamidementioning
confidence: 99%
“…26 -29 Use of procainamide in cardiac arrest is supported by only a retrospective comparison study involving only 20 patients. 120 Procainamide administration in cardiac arrest is limited by the need for slow infusion and uncertain efficacy in emergent circumstances.…”
Section: Shocks Must Not Be Delayed Until An IV Line Is Established Amentioning
confidence: 99%
“…The evidence that supported this change is dated and of low quality, but the weight of evidence at the time argued against any benefit in such cases. [103][104][105] Since the publication of the 2010 AHA guidelines, a study from the Survey of Survivors of Cardiac Arrest in the Kanto Area (SOS-KANTO) Study Group was published that compared the efficacy of epinephrine and epinephrine plus atropine for patients presenting with pulseless electric activity or asystole. There was no benefit from atropine plus epinephrine compared with epinephrine alone for patients presenting with pulseless electric activity as measured by rate of ROSC, survival to hospital admission, 30-day survival, or 30-day favorable neurological outcome.…”
Section: Advances In Pharmacotherapy For Scdmentioning
confidence: 99%